2020
DOI: 10.1039/c9bm01524h
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation improves chondrogenesisin vitroand cartilaginous matrix stabilityin vivocompared to bulk encapsulation

Abstract: The encapsulation of cells into microgels is attractive for applications in tissue regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 52 publications
1
61
0
Order By: Relevance
“…Therefore, building on the translational (i.e., formulated products and hundreds of treated patients) and transpositional (i.e., multiple GMP technology transfers) hindsight gathered for cutaneous regenerative medicine, and given the highly similar behaviors and characteristics of hECPs from the same organ donation (i.e., FE002), the high potential value with regard to sustainability and quality assurance of the FE002-Cart cell type are assured [34]. Furthermore, to complement the preliminary safety data presented herein, additional work of collaborator groups around the same hECP cell source have preliminarily confirmed safety in alternate preclinical models (i.e., nude, NSG, NSG-SGM3, and C57BL/6 murine subcutaneous implantation models), along with potential modulation of chondrogenic activity by physical and chemical cues [12,64,92,94]. Overall, it had been shown in at least three in vivo studies that considered hECPs (i.e., same source from cell banks established in our laboratory) could be implanted in immunocompromised, humanized, and immunocompetent mice without the formation of tumors or rejection of implanted materials.…”
Section: Safetymentioning
confidence: 67%
See 1 more Smart Citation
“…Therefore, building on the translational (i.e., formulated products and hundreds of treated patients) and transpositional (i.e., multiple GMP technology transfers) hindsight gathered for cutaneous regenerative medicine, and given the highly similar behaviors and characteristics of hECPs from the same organ donation (i.e., FE002), the high potential value with regard to sustainability and quality assurance of the FE002-Cart cell type are assured [34]. Furthermore, to complement the preliminary safety data presented herein, additional work of collaborator groups around the same hECP cell source have preliminarily confirmed safety in alternate preclinical models (i.e., nude, NSG, NSG-SGM3, and C57BL/6 murine subcutaneous implantation models), along with potential modulation of chondrogenic activity by physical and chemical cues [12,64,92,94]. Overall, it had been shown in at least three in vivo studies that considered hECPs (i.e., same source from cell banks established in our laboratory) could be implanted in immunocompromised, humanized, and immunocompetent mice without the formation of tumors or rejection of implanted materials.…”
Section: Safetymentioning
confidence: 67%
“…Non-toxic and no angiogenesis perturbation in CAM 5 model 1 Non-immunogenic and non-tumorigenic in murine and rat models of cartilage defect or subcutaneous implantation Non-immunogenic, non-tumorigenic, and no slowing of cartilage defect healing in caprine model 1 [36,92] Functionality Spontaneous chondrogenic activity in 3D micropellets Potent and stable production of ECM 6 (i.e., GAGs 7 , aggrecan, types I and II collagen) Important functional responsiveness to mechanostimulation in dynamic scaffold culture conditions Highly responsive chondrogenic potential under biochemical stimulation (e.g., alginate, TGF-β1) Highly responsive chondrogenic potential in specific formulations (e.g., therapeutic cell microencapsulation) [12,34,36,70,92,94] Overall, the most interesting aspect of the Swiss FPC transplantation program is the initial requirement for only one single organ donation following a controlled and medically indicated pregnancy termination, for the parallel establishment of progenitor cell types from different tissues, among which is epiphyseal cartilage. From the same initial organ donation (i.e., FE002, 2009), dermal progenitor cell sources had been established, and the overall framework biobanking model was established and validated using this source in industrialized and clinical settings [30,41].…”
Section: Safetymentioning
confidence: 99%
“…Figures modified with permission from Hirt-Burri et al (2011) and Lapp et al (2013). Li et al, 2020). Scaffold stiffness improves with ECM deposition and may approach physiological ranges in clinically relevant timeframes (Broguiere et al, 2016).…”
Section: Phenotypic Stability Chondrogenic Potential and Biomechanicsmentioning
confidence: 99%
“…This is similar to our previous study in which MSCs, as well as other cell types, migrated to the periphery of microgels. [16][17][18]33 We hypothesize that this may be due to the cells actively sensing higher mass transfer and higher nutrient concentrations at the surface of the microgels, thus migrating to the surface. In addition, this data suggests that the reduced amount of gelatin in the Gel:HA hydrogels was still sufficient to support adequate cell adhesion and spreading similar to that of gelatin alone with a change of total weight percentage from 4 to 2%.…”
Section: Cell Viability and Morphologymentioning
confidence: 99%
“…16−18 In addition, due to their smaller size, they can be readily injected to the defect site through a minimally invasive procedure. 9,[16][17][18]21 Microfluidic techniques for cell encapsulation in microgels are gaining much attention as an effective means to rapidly generate monodisperse microgels of varying sizes as this can be achieved by simply manipulating the flow rates of immiscible liquids or altering the dimensions of the channels. 19 Several studies have reported promising application of cell-laden microgels for bone regeneration purposes using biomaterials such as gelatin, 9,22 alginate, 23 and polyvinyl alcohol (PVA).…”
Section: Introductionmentioning
confidence: 99%